Respuesta :

Answer:

The solution of the system is the point (-2,4)

Step-by-step explanation:

we have

[tex]2x-\frac{3}{4}y=-7[/tex] ---> equation A

[tex]x+\frac{1}{2}y=0[/tex] ----> equation B

Solve the system by elimination

Multiply the equation B by -2 both sides

[tex]-2(x+\frac{1}{2}y)=-2(0)[/tex]

[tex]-2x-y=0[/tex] ----> equation C

Adds equation A and equation C

[tex]2x-\frac{3}{4}y=-7\\-2x-y=0\\--------\\\\-\frac{3}{4}y-y=-7\\\\-\frac{7}{4}y=-7\\\\y=4[/tex]

Find the value of x

substitute the value of y in any equation

[tex]x+\frac{1}{2}(4)=0[/tex]

[tex]x+2=0[/tex]

[tex]x=-2[/tex]

The solution of the system is the point (-2,4)